The Practicality and Effectiveness of the Chemical Snakes and Ladders Game on Acid-Base Material on the Learning Outcomes of Class XI SMA/MA Students - Marina Lantusia; Iswendi Iswendi (Universitas Riau, 2023)
This research was motivated by the availability of the chemical ladder snake game as a medium for learning acid-base material developed by Amalia Putri Lubis & Iswendi. It is valid but not tested for practicality and effectiveness. This study aims to determine the suitability and effectiveness of the chemical snakes and ladders game. This type of research is a continuation of development research with a Pretest-Posttest Control Group Design and is a 4-D model development. The research population is class XI MIPA students of SMAN 1 Ranah Batahan. Samples takeusing by Simple Random Sampling technique. The research instruments were useful questionnaires and learning achievement tests. The data analysis technique is the practicality percentage technique and the N-Gain test and t-test. The results of the data analysis of practicality are, at a convenient level, for effectiveness the results of data analysis show pretty effective. This is evidenced by the N-Gain percentage of the experimental class of 66% at a somewhatadequate level and the control class of 47% at a less practical level, and supported by hypothesis testing with the t-test, namely tcount (2.6686)> table (2.0106) at the real level α = 0.05 with dk = 48 and chance t0.95.